Hepatitis C Virus Transmission Among Men Who Have Sex With Men in Amsterdam: External Introductions May Complicate Microelimination Efforts. (8th December 2020) - Koopsen, Jelle; Parker, Edyth; Han, Alvin X; van de Laar, Thijs; Russell, Colin; Hoornenborg, Elske; Prins, Maria; van der Valk, Marc; Schinkel, Janke
Abstract: Background: It is unclear whether unrestricted access and high uptake of direct-acting antivirals (DAAs) is sufficient to eliminate hepatitis C virus (HCV) in high-risk populations such as men who have sex with men (MSM). This study presents historic trends and current dynamics of HCV transmission among MSM in Amsterdam based on sequence data collected between 1994 and 2019. Methods: Hypervariable region 1 sequences of 232 primary HCV infections and 56 reinfections were obtained from 244 MSM in care in Amsterdam. Maximum-likelihood phylogenies were constructed for HCV genotypes separately, and time-scaled phylogenies were constructed using a Bayesian coalescent approach. Transmission clusters were determined by Phydelity and trends in the proportion of unclustered sequences over time were evaluated using logistic regression. Results: Seventy-six percent (218/288) of sequences were part of 21 transmission clusters and 13 transmission pairs. Transmission cluster sizes ranged from 3 to 44 sequences. Most clusters were introduced between the late 1990s and early 2010s and no new clusters were introduced after 2012. The proportion of unclustered sequences of subtype 1a, the most prevalent subtype in this population, fluctuated between 0% and 20% in 2009–2012, after which an increase occurred from 0% in 2012 to 50% in 2018. Conclusions: The proportion of external introductions of HCV infections among MSM in Amsterdam has recently increased, coinciding with high DAA uptake. Frequent international transmission events will likely complicate local microelimination efforts. Therefore, international collaboration combined with international scale-up of prevention, testing, and treatment of HCV infections (including reinfections) is warranted, in particular for local microelimination efforts. Abstract : To eliminate hepatitis C virus (HCV) transmission among men who have sex with men (MSM), knowledge on transmission dynamics is required. This study suggests, using viral sequence data, that new HCV infections are increasingly externally obtained among MSM in Amsterdam, which may impede achieving microelimination goals.